Edge of Enterprise Architecture in Addressing Cyber Security Threats and Business Risks - Judijanto, Loso; Hindarto, Djarot; Wahjono, Sentot Imam; Djunarto (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2023)
Enterprise Architecture plays a critical role in reducing business risks holistically and ensuring a company's resilience to cyber security threats. This abstract emphasizes the significance of Enterprise Architecture in contemporary organizational structures and its influence on these matters, particularly at a time when cybersecurity threats are becoming more prevalent in the global business arena. By integrating Human Resources, Governance Frameworks, Technology, and Processes, Enterprise Architecture offers a holistic perspective of the Information Technology environment within an organization. By means of a methodical governance framework, Enterprise Architecture conducts comprehensive examinations of interdependencies among components, detects susceptibilities, and establishes robust groundwork for enhanced threat prevention. Enterprise Architecture is not only a proactive risk management tool, but it also contributes significantly to the overall business strategy. The integration of cybersecurity and enterprise architecture entails not only fortifying the technological infrastructure but also integrating it into the overarching business strategy. This enables the correlation of cybersecurity endeavors with the objectives of the organization, thereby connecting technological aspirations with business strategy. This study emphasizes the potential of incorporating adaptive and agile responses to threats into corporate culture to foster innovation. By functioning as a strategic catalyst, it assists organizations in adjusting to cyber threats, safeguarding business interests, and optimizing operations within an ever-evolving digital environment. By integrating governance and enterprise architecture frameworks, organizations can proactively mitigate business risks and cybersecurity threats, thereby fostering resilience and sustainability in the dynamic digital environment.